2005
DOI: 10.1002/ana.20513
|View full text |Cite
|
Sign up to set email alerts
|

Functional anatomy of the basal ganglia in X‐linked recessive dystonia‐parkinsonism

Abstract: Dystonia is a neurological syndrome characterized by sustained muscle contractions that produce repetitive twisting movements or abnormal postures. X-linked recessive dystonia parkinsonism (XDP; DYT3; Lubag) is an adult-onset disorder that manifests severe and progressive dystonia with a high frequency of generalization. In search for the anatomical basis for dystonia, we performed postmortem analyses of the functional anatomy of the basal ganglia based on the striatal compartments (ie, the striosomes and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
171
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(178 citation statements)
references
References 47 publications
7
171
0
Order By: Relevance
“…Differential degeneration of striosomes has been found in a postmortem analysis of the brains of DYT3 patients (33). Thus an important question to pursue is whether some dystonias are linked to a disproportionate loss of normal activity in the striosome compartment, and whether their hypokinetic or hyperkinetic character depends on the associated dopaminergic activities in the matrix compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Differential degeneration of striosomes has been found in a postmortem analysis of the brains of DYT3 patients (33). Thus an important question to pursue is whether some dystonias are linked to a disproportionate loss of normal activity in the striosome compartment, and whether their hypokinetic or hyperkinetic character depends on the associated dopaminergic activities in the matrix compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Goto et al [13] identified loss of calcineurinexpressing neurons with accompanying gliosis in the striosome compartment in the early stage of XDP. They proposed that selective neuronal death within the striatum might result in an imbalance in activity between the striosomal and matrix-based pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunction of striatal matrix neurons is especially severe for the indirect pathway neurons of the striatum, which in the sensorimotor striatum receive powerful inputs from the motor cortex (4)(5)(6). In different models of parkinsonian states, the gradients and compartmental expression of dopaminergic deficits vary (7)(8)(9), but it seems likely that dysfunctional dopaminergic modulation of corticostriatal motor pathways leading through the matrix compartment is a major contributor to the motor symptoms of Parkinson's disease, and that in a range of movement disorders, compartmentally selective striatal dysfunction is present (10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%